International legal mechanisms to protect the environment from climate change - Alotaebi, Abdulmajeed Motib (Journal of Economic, Administrative and Legal Sciences, 2025)
The topic of environmental pollution encompasses significant aspects of importance and is one of the most pressing global challenges. This phenomenon is worsening over time and poses a barrier to the entire world's population, especially with the increasing development and progress in the near and distant future in industrial wealth and competitive desires among nations to build resources.The efforts of the United Nations in this field have led to the establishment of several conferences that resulted in numerous outcomes, such as the United Nations Conference on the Human Environment in 1972, which was the first UN conference that contributed to the establishment of principles and rules of international environmental law through the Stockholm Declaration on the Human Environment.Moreover, the Rio Conference in 1992 marked a pivotal point in the development of international environmental law by linking the environment to development through the Rio Declaration and the signing of key environmental agreements, including the Convention on Biological Diversity and the Climate Change Convention of 1992.The researcher aims in this study to shed light on the issues surrounding international environmental matters and to clarify the importance of cooperation and the legal mechanisms necessary for the protection of the international environment.
Keywords: United nations organization; Environmental pollution; protection of the international environment; international environmental law